DEGREE OF INTEGRITY AND AVAILABILITY OF TEACHERS WITH THE IMPLEMENTATION OF ASSESSMENT-BASED PRIMARY SCHOOL - Abdul Said Ambotang; Shanti Gobalakrishnan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study was undertaken to identify the relationship between the level of integrity and availability of teachers with the implementation of school-based assessment in primary schools .This study uses quantitative methods to determine the relationship between the independent variable (the level of integrity and availability of teachers) with the dependent variable (Based Assessment School). The sample was obtained from teachersâ€™ primary school in Tawau, Sabah. A total of 360 samples have been obtained by the investigators to be tested in this study. Each hypothesis was tested using the Statistical Package for Social Sciences (SPSS) version 22.0. The study found a significant relationship at the highest level is r = 0.788 between the variable level of integrity the implementation of school-based assessment, a significant relationship at high level r = 0818 between variables and teacher of the knowledge of teachers and the implementation of school-based assessment, The study also found that there was a high, strong and very significant between the willingness of teachers with teachers’ understanding of aspects of the implementation of school-based assessment r = 0.852